2008
DOI: 10.1049/el:20081562
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stereoscopic video quality using objective quality models of 2-D video

Abstract: The timely deployment of 3-D video applications requires accurate objective quality measures, so that time consuming subjective tests can be avoided.Investigates is the correlation between subjective and objective evaluations of colour plus depth map 3-D video. The investigation is conducted for different compression ratios. Subjective tests are performed to determine the overall image quality and depth perception of a range of asymmetrically coded video sequences. The subjective results are used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…Therefore the proposed technique cannot overcome the initial loss, which is about 2.5dB that it endured at the encoding process. However as shown in [10], for reasonable quality 3D viewing experience, the Color image quality is much important than the depth image quality. Therefore even for low motion sequences such as 'Interview', this technique can still be employed over the original method since the proposed method achieves better color quality at high packet loss environments, at the loss of depth image quality.…”
Section: B Discussion Of Resultsmentioning
confidence: 99%
“…Therefore the proposed technique cannot overcome the initial loss, which is about 2.5dB that it endured at the encoding process. However as shown in [10], for reasonable quality 3D viewing experience, the Color image quality is much important than the depth image quality. Therefore even for low motion sequences such as 'Interview', this technique can still be employed over the original method since the proposed method achieves better color quality at high packet loss environments, at the loss of depth image quality.…”
Section: B Discussion Of Resultsmentioning
confidence: 99%
“…By fusing the obtained the quality index of each view image, the quality value of the stereoscopic image is determined. In [39], Hewage et al investigated the correlation between subjective quality scores and three quality metrics, including PSNR, Video Quality Model (VQM) [40], and SSIM [10] for 3D video content. It is demonstrated that the VQM metric performs better than the other two metrics for predicting the overall perceptual quality of the stereoscopic image.…”
Section: Related Workmentioning
confidence: 99%
“…The study is evaluated that the FR metric of 2D quality assessment can be used for an extension to 3D.Though the PSDR is a simple and widely used image quality objective evaluation indicators but the relevance to visual quality is very poor. Although, the impact of coding distortions on the perceived stereoscopic image quality of an asymmetric image pair depends on the visual appearance of the artifact, where blockiness appears to be much more disturbing than other factors [12].That is to say, the extent of blockiness can be used as a main evaluation indicator of image distortion. In [7], firstly a differencing signal along each horizontal line is calculated.…”
Section: 31video Qualitymentioning
confidence: 99%
“…They concluded Parallax is the key factors of stereoscopic image have stereo feeling and will directly affect the quantity of the three-dimensional images. In [12], the quality of 3D videos stored as monoscopic color videos that augmented by pixel depth map and finally this pixel information used for color coding and depth data. The relationship between the perceived overall image quality and the perceived depth are discussed in [13].…”
Section: D Depth Perceptionmentioning
confidence: 99%